The Training Setting as a Social and Liminal Space for Professional Hybridization - Scaratti, Giuseppe; Fregnan, Ezio; Ivaldi, Silvia (Frontiers in Psychology, 2021)
The paper addresses the use of liminality concept to explore a particular group context, relating to a training setting intended as a liminal space, highlighting its potential to trigger evolutionary personal and organizational identity trajectories. Dealing with a contemporary uncertain, volatile and ambiguous organizational scenario, people are asked to consistent and quick professional hybridization processes. The paper refers to a case study related to an action research process aimed at a cultural transformation and nurturing organizational learning inside an extra-hospital Rehabilitation Center, challenged by a strong organizational reconfiguration and the creation of new functions and roles, among which the one of coordinator, responsible for the operational activity to be managed within units of the organizational context. The paper highlights both the mains features that characterize a training setting as a liminal space, and identifies possible plots of professional hybridization paths that a training group as a liminal space can trigger and develop.